Formulation and Antimicrobial Evaluation of Isopropyl Hand Sanitizer using Co-processed Excipients (2020)
Background: In response to the Ebola virus outbreak in West Africa in the year 2014, which caused the Ebola haemorrhagic fever, the WHO alcohol-based hand rub formulation was adopted in addition to regular hand washing to prevent the spread. However, other formulation factors rather than alcohol concentration alone can greatly influence the overall antimicrobial efficacy of hand disinfectants. Objective: To formulate an antimicrobial hand sanitizer using co-processed carriers. Methodology: Carbopol (F), HPMC (G) and co-processed forms of both polymers in batches- 1:1(A), 1:2(B), 1:4(C), 2:1(D) and 4:1(E) respectively were used. The polymers were characterized, and used as carriers in formulating hand sanitizers (A to G). The formulated hand sanitizers were evaluated for physical appearance, pH, clarity, viscosity, drying time and antimicrobial activity, in comparison to a commercially available hand sanitizer (CAHS). Results: Co-processing significantly (p0.05) improved both hydration capacity of carbopol and viscosity of HPMC. The physical appearance, pH and opacity were maintained throughout the study. All the formulations showed dilatant rheological behaviour while the CAHS exhibited plastic flow. The drying times for the formulated hand sanitizers were comparable to CAHS but longer than isopropyl alcohol implying prolonged action at application site. The antimicrobial activity of the formulations was of the rank order isopropyl alcohol>B>F>CAHS>D>E>C>G>A. Conclusion: Co-processing of excipients improved the pharmaceutical properties of the hand sanitizers with antimicrobial activity that was comparable to CAHS but lower than isopropyl alcohol. The hand sanitizer formulated with polymer batch B, demonstrated optimum antimicrobial and pharmaceutical properties and may be developed for commercial use.